PENGARUH BUDAYA ORGANISASI DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PT. SUMBER REZEKI BERSAMA - HILMAN LUBIS (JURNAL ILMIAH KOHESI, 2021)
The purpose of this study was to determine the effect of Organizational Culture on Employee Performance at PT SumberRezeki Bersama, to know the Effect of Organizational Climate on Employee Performance at PT Sumber Rezeki Bersamaand to know the effect of Organizational Culture and Organizational Climate simultaneously on Employee Performance atPT Sumber Rezeki Bersama Medan. This research is a descriptive quantitative research with a questionnaire instrumentcarried out on all employees of PT Sumber Rezeki Bersama Medan totaling 85 people. Furthermore, using total sampling,the sample size of this study amounted to 85 people. The result of the research is that organizational culture partially has asignificant effect on the performance of the employees of PT Sumber Rezeki Bersama Medan of 2.368. Organizationalclimate partially has a significant effect on Employee Performance at PT Sumber Rezeki Bersama Medan amounting to5.824 and simultaneously there is a significant influence between Organizational Culture and Organizational Climate onEmployee Performance at PT Sumber Rezeki Bersama Medan. The conclusion of the study is that organizational culturepartially has a significant effect on the performance of employees of PT Sumber Rezeki Bersama with a sig value <0.05,Organizational climate is partially significant and is the dominant variable that affects the performance of employees ofPT Sumber Rezeki Bersama Medan, with a sig <0 , 05 and organizational culture and organizational climate simultaneouslyhave a significant effect on the performance of employees of PT Sumber Rezeki with Medan, with a sign value <0.05.